Gyrokinetic study of turbulence suppression in a JET-ILW power scan. (15th September 2016) - Doerk, H; Challis, C; Citrin, J; Garcia, J; Görler, T; Jenko, F
Abstract: For exploring tokamak operation regimes that deliver both high β and good energy confinement, power scans at JET with ITER-like wall have been performed. Relatively weak degradation of the confinement time coincides with increased core temperature of the ions at high power. The changes in core turbulence characteristics during a power scan with an optimized (broad) q profile are analyzed by means of nonlinear gyrokinetic simulations. The increase in β is crucial for stabilizing ion temperature gradient driven turbulence, accompanied by increased ion to electron temperature ratio, the presence of a dynamic fast ion species, as well as the geometric stabilization by increased thermal and suprathermal pressure. A sensitivity study with respect to the q profile reveals that electromagnetic effects are more pronounced at larger values of q . Further, it is confirmed that turbulence suppression due to rotation becomes less effective in such strongly electromagnetic systems. Electrostatic simplified models may thus perform well in present-day devices, in which high β is often correlated with high rotation, but provide poor extrapolation towards low rotation devices. Implications for ITER and reactor plasmas are discussed.